Chronic Constipation in the Community: A National Survey of Australian Adults. Issue 3 (May 2020) - Werth, Barry L.; Fisher, Murray J.; Williams, Kylie A.; Pont, Lisa G.
Abstract : PURPOSE: The aim of this study was to determine the prevalence of chronic constipation and identify factors associated with chronic constipation in community-dwelling adults. DESIGN: Cross-sectional study. METHODS: The target population was community-dwelling Australian adults; 1978 participants completed an online questionnaire exploring symptoms, management, and factors potentially associated with constipation. Chronic constipation was identified using Rome III criteria. Multivariate logistic regression model was used to identify factors associated with chronic constipation. RESULTS: The prevalence of chronic constipation was 23.9%. Factors significantly associated with chronic constipation in the multivariate model were female gender (odds ratio [OR] = 1.42, 95% confidence interval [CI], 1.12-1.81), current employment (OR = 1.45, 95% CI, 1.11-1.88), regular smoking (OR = 1.60, 95% CI, 1.19-2.14), poor self-rated health (OR = 2.57, 95% CI, 1.28-5.19), thyroid disease (OR = 1.77, 95% CI, 1.21-2.79), depression (OR = 1.49, 95% CI, 1.08-2.06), hemorrhoids (OR = 2.98, 95% CI, 1.84-4.83), irritable bowel syndrome (OR = 2.45, 95% CI, 1.73-3.46), and use of anti-inflammatory/antirheumatic medications (OR = 2.06, 95% CI, 1.15-3.68). In contrast to these factors, use of medications acting on the renin-angiotensin system was associated with a reduced likelihood of chronic constipation (OR = 0.47, 95% CI, 0.24-0.91). CONCLUSIONS: Chronic constipation is prevalent among community-dwelling adults. Various factors associated with chronic constipation have been identified, and knowledge of these factors may help health care professionals recognize individuals who are at high risk of chronic constipation. Abstract : Supplemental Digital Content is Available in the Text.